2018
DOI: 10.1056/nejmoa1800820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dengue Serostatus on Dengue Vaccine Safety and Efficacy

Abstract: CYD-TDV protected against severe VCD and hospitalization for VCD for 5 years in persons who had exposure to dengue before vaccination, and there was evidence of a higher risk of these outcomes in vaccinated persons who had not been exposed to dengue. (Funded by Sanofi Pasteur; ClinicalTrials.gov numbers, NCT00842530 , NCT01983553 , NCT01373281 , and NCT01374516 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
532
1
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(568 citation statements)
references
References 21 publications
18
532
1
17
Order By: Relevance
“…Since the isolation of DENV in 1943, the development of an effective vaccine that provides balanced, long‐lasting immunity has been challenging. This is partly due to the complexity of dengue epidemiology, population immunity, and the interplay between viral pathogenesis and host immunological mechanisms . Like other successful flavivirus vaccines against yellow fever and Japanese encephalitis, the majority of dengue vaccine candidates either approved for limited license or in Phase III trials are LAVs .…”
Section: Introductionmentioning
confidence: 99%
“…Since the isolation of DENV in 1943, the development of an effective vaccine that provides balanced, long‐lasting immunity has been challenging. This is partly due to the complexity of dengue epidemiology, population immunity, and the interplay between viral pathogenesis and host immunological mechanisms . Like other successful flavivirus vaccines against yellow fever and Japanese encephalitis, the majority of dengue vaccine candidates either approved for limited license or in Phase III trials are LAVs .…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that vaccine performance was indeed affected by serostatus, with vaccine efficacy being significantly higher in seropositives than seronegatives. Furthermore, an increased risk of hospitalized, severe dengue was observed among seronegative vaccine recipients as compared to seronegative controls (Sridhar et al 2018). In light of this new evidence regarding vaccine-related ADE, WHO-SAGE issued updated recommendations on the use of CYD-TDV vaccine in April 2018 (Wilder-Smith et al 2019).…”
Section: Implications For Dengue Vaccinesmentioning
confidence: 99%
“…A recent study added to the growing safety concerns by demonstrating that in seronegative vaccine recipients the risk of hospitalisation and severe dengue was higher than in individuals who were seropositive at baseline regardless of age . In this study, all cases of virologically confirmed dengue were reassessed for hospitalisation and severe dengue by serostatus and age groups.…”
mentioning
confidence: 97%
“…The increased risk of more severe infection in seronegative vaccine recipients was observed up to 30 months after vaccination. In contrast, vaccine efficacy in all age groups was significantly higher in seropositive individuals (76%) compared with seronegative individuals (39%) . Based on these findings, the World Health Organization reconvened SAGE and in 2018 revised the recommendations for the use of CYD‐TDV (Box 1).…”
mentioning
confidence: 99%